26t-61=971

Simple and best practice solution for 26t-61=971 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26t-61=971 equation:


Simplifying
26t + -61 = 971

Reorder the terms:
-61 + 26t = 971

Solving
-61 + 26t = 971

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '61' to each side of the equation.
-61 + 61 + 26t = 971 + 61

Combine like terms: -61 + 61 = 0
0 + 26t = 971 + 61
26t = 971 + 61

Combine like terms: 971 + 61 = 1032
26t = 1032

Divide each side by '26'.
t = 39.69230769

Simplifying
t = 39.69230769

See similar equations:

| .875+.25x=5x | | 12.73+.06h=13.48+.14h | | 8m+10n=-4 | | 2(3x+2)=5(X-4) | | X^2-6x+y^2=0 | | -5(r+3)=56 | | 11(12+14)+15(14-5x)=263 | | 3y+3x+15=0 | | 2lx+2l^2=72 | | 9x-19=4x+7 | | 10x+25=3x(x) | | 7x+11=0 | | 2x^2-4x-27=3 | | -7(-n+2t)=-16+7n | | -3x+8=9x-28 | | -3+8=9x-28 | | 3x+422x=2x+2 | | 0.16x+0.8(x-2)=0.01(2x-5) | | 5a(a-5)(a+6)= | | 5x-15=7x+6 | | 135=-1+68x | | 23-3z=2 | | 8x+19=11x+28 | | 16t+14=0 | | 6p+5c= | | r^2-6t-3tr+2r= | | 8a+4b-7a-3b= | | -18+x=8*x | | 7x-5=6x-2 | | 6(t-4)+6t=6(2t+4)-8 | | 4x+3y=1-3y | | 4(2x+7)=8x+28 |

Equations solver categories